EVALUASI PERUBAHAN SAK ETAP KE SAK EP TERHADAP LAPORAN KEUANGAN PADA KOPERASI BHAKTI KARYA DI PERKEBUNAN SENTOOL, KOTA JEMBER - Saputri, Agustina Eka; Yuliarti, Norita Citra; Suharsono, Riyanto Setiawan (Jurnal Mahasiswa Entrepreneurship (JME), 2022)
Cooperatives as one of the entities that use SAK ETAP are expected to know the functions and ease of use of SAK ETAP in preparing financial reports. By using descriptive qualitative, namely collecting data, analyzing data, and concluding data analysis. Collecting data by conducting interviews, documentation and observation. The financial statements in accordance with SAK ETAP consist of, profit and loss statements, balance sheets, cash flow statements, and notes to financial statements which are the basis for the evaluation and presentation of SAK ETAP financial statements. So the results of this study, where the Notes to the financial statements have not been presented by the Cooperative due to a lack of understanding on how to do it and because the reports have been adapted to the needs of those who work within the cooperative rather than compiled according to the relevant ones. ETAP SAK. And still have not implemented SAK EP.